Aquatic macrophyte ﬂora of coastal lakes in Santa Catarina, southern Brazil - Ferreira, João Paulo Ramos; Hassemer, Gustavo; Trevisan, Rafael (Iheringia, Série Botânica., 2018)
Aquatic macrophytes are representative fl ora elements of diverse wetland environments. They play several roles in aquatic ecosystems and are components of paramount importance in maintaining the dynamic and quality of these environments. For coastal lakes, where most aquatic macrophyte studies have been conducted, fl oristic surveys are continuously increasing, resulting in more knowledge about these species. This study sought to increase what is known about aquatic macrophytes by inventorying the biodiversity of these plants in three coastal lakes in the cities of Florianópolis (Lake Pequena), Imbituba (Lake Doce) and Araranguá (Lake Azul), Santa Catarina. A total of 112 aquatic macrophyte species were identifi ed, including 76 species for Lake Pequena, 50 for Lake Doce and 52 for Lake Azul. Among the most representative families, Cyperaceae (24 species), Poaceae (10) and Onagraceae (eight) are notable.